The Essence of Fuel and Energy Consumptions to Stimulate MSMEs Industries and Exports: An Empirical Story for Indonesia - Wijaya, Adi; Awaluddin, Muhammad; Kurniawan, A. Erwin (International Journal of Energy Economics and Policy, 2022)
Economics and the environment are issues that never end for debate. As long as the two are not sustainable, they will continue to be highlighted in macroeconomic principles. In addition, economic growth (GDP) is not the only principal topic that is the focus of attention from academics, practitioners, and the government. The objectivity of this research is to dissect the relationship between coal consumptions, electricity consumptions, and oil consumptions on MSMEs and contributors of exports of goods and services in Indonesia. Path analysis supports the test instrument. We implement secondary data to cover seven periods (2014-2020). Regarding the research flow, there are three problem formulation packages that must be investigated, including two direct paths and mediation pathways. The identification results report several important inventions. Coal consumptions and oil consumptions have triggered a positive increase in MSMEs and contributors to exports of goods and services. From another scope, electricity consumption as empirical evidence that affects the contribution of exports of goods and services through MSMEs. The findings of this study provide valuable insights into the sustainability of the MSME industry, creating added value for Indonesian exports, without ignoring regulations related to fuel and energy.